2015
DOI: 10.1186/s40478-015-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

The domestic cat as a natural animal model of Alzheimer’s disease

Abstract: IntroductionAlzheimer’s disease (AD) is the most dominant neurodegenerative disorder that causes dementia, and no effective treatments are available. To study its pathogenesis and develop therapeutics, animal models representing its pathologies are needed. Although many animal species develop senile plaques (SP) composed of amyloid-β (Aβ) proteins that are identical to those found in humans, none of them exhibit neurofibrillary tangles (NFT) and subsequent neurodegeneration, which are integral parts of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 60 publications
(78 reference statements)
8
75
2
Order By: Relevance
“…Many mammals, including wild-type mice, do not develop spontaneously NFTs during aging, but the development of a tau pathology is not specific to human species. Abnormal tau phosphorylation is also described in other aged mammals (Hartig et al, 2000;Youssef et al, 2016), such as cats (Chambers et al, 2015;Gunn-Moore et al, 2006;Head et al, 2005), dogs (Papaioannou et al, 2001;Yu et al, 2011), sheep (Braak et al, 1994a;Nelson et al, 1994;Reid et al, 2017), octogon degu (van Groen et al, 2011), brown bears (Cork et al, 1988), lemurian Microcebus (Bons et al, 1995), and cynomolgus monkeys (Oikawa et al, 2010;Uchihara et al, 2016), in the presence (Chambers et al, 2015;Cork et al, 1988;Gunn-Moore et al, 2006;Head et al, 2005;Oikawa et al, 2010;Papaioannou et al, 2001;Reid et al, 2017;Uchihara et al, 2016;van Groen et al, 2011;Yu et al, 2011), as well as in the absence (Braak et al, 1994a;Nelson et al, 1994), of Ab deposits. In cats, a previous study concluded that phosphorylated tau proteins, composed of both 3R and 4R isoforms, formed aggregates only in the presence of amyloid (Chambers et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Many mammals, including wild-type mice, do not develop spontaneously NFTs during aging, but the development of a tau pathology is not specific to human species. Abnormal tau phosphorylation is also described in other aged mammals (Hartig et al, 2000;Youssef et al, 2016), such as cats (Chambers et al, 2015;Gunn-Moore et al, 2006;Head et al, 2005), dogs (Papaioannou et al, 2001;Yu et al, 2011), sheep (Braak et al, 1994a;Nelson et al, 1994;Reid et al, 2017), octogon degu (van Groen et al, 2011), brown bears (Cork et al, 1988), lemurian Microcebus (Bons et al, 1995), and cynomolgus monkeys (Oikawa et al, 2010;Uchihara et al, 2016), in the presence (Chambers et al, 2015;Cork et al, 1988;Gunn-Moore et al, 2006;Head et al, 2005;Oikawa et al, 2010;Papaioannou et al, 2001;Reid et al, 2017;Uchihara et al, 2016;van Groen et al, 2011;Yu et al, 2011), as well as in the absence (Braak et al, 1994a;Nelson et al, 1994), of Ab deposits. In cats, a previous study concluded that phosphorylated tau proteins, composed of both 3R and 4R isoforms, formed aggregates only in the presence of amyloid (Chambers et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Identical paired helical filaments have been described in an older chimpanzee (discussed above), but not yet in any other primate species. Naturally occurring tauopathies have also been reported in several nonprimate species, including bears [85], cats [86], goats, and cattle [87, 88], but these conditions do not resemble AD pathologically.…”
Section: Why Has Ad Not Been Identified In Nonhuman Species?mentioning
confidence: 99%
“…Similarly, some studies report AT8reactive pTau in aged vervets [12], others detected either no or different pTau epitopes in rhesus monkeys or marmosets [18,19]. It will be of interest to apply our current investigation not only to larger samples, but also to additional species, for example cats [20], that could be used as novel alternative models for the study of AD neuropathologic change.…”
mentioning
confidence: 75%